Chromosomal integration and plasmid fusion occurring in ST20 carbapenem-resistant Klebsiella pneumoniae isolates coharboring blaNDM-1 and blaIMP-4 induce resistance transmission and fitness variation - Qiucheng Shi; Huangdu Hu; Qian Yu; Weiyi Huang; Yinping Wang; Jingjing Quan; Junxin Zhou; Rui Weng; Ping Zhang; Yan Meng; Haiyang Liu; Yan Jiang; et al. (Emerging Microbes and Infections)
To investigate the epidemiology of ST20 carbapenem-resistant Klebsiella pneumoniae (CRKP) in China, and further explore the genomic characteristics of blaIMP-4 and blaNDM-1 coharboring isolates and plasmid contributions to resistance and fitness. Seven ST20 CRKP isolates were collected nationwide, and antimicrobial susceptibility testing was performed. Antimicrobial resistance genes, virulence genes, and plasmid replicons were identified via whole-genome sequencing, and clonality assessed via core-genome multilocus sequence typing. Furthermore, we found four dual-metallo-β-lactamases (MBL)-harbouring isolates, the gene location was detected by Southern blotting, and plasmid location analysis showed that blaIMP-4 was located on a separate plasmid, a self-conjugative fusion plasmid, or the bacterial chromosome. These isolates were subjected to long-read sequencing, the presence of blaIMP-4 in different locations was identified by genomic comparison, and transposon units were detected via inverse PCR. We subsequently found that blaIMP-4 on the fusion plasmid and bacterial chromosome was formed via intact plasmid recombination by the IS26 and ltrA, respectively, and the circular transposon unit was related to cointegration, however, blaIMP-4 in different locations did not affect the gene stability. The blaNDM-1-harbouring plasmid contributed to the increased resistance to β-lactams and shortened survival lag time which was revealed in plasmid cured isolates. In summary, the K. pneumoniae ST20 clone is a high-risk resistant clone. With the use of ceftazidime/avibactam, MBL-positive isolates, especially dual-MBL-harbouring isolates, should be given additional attention.